Central Airway Carcinoid Tumorlets Following Resection of a Typical Carcinoid Tumor - Kyungsoo Bae; Kyung Nyeo Jeon; I Re Heo; Hyo Jung An; Dae Hyun Song (Diagnostics, 2025)
Pulmonary neuroendocrine proliferations and neoplasms represent a broad spectrum of diseases, ranging from neuroendocrine cell hyperplasia and tumorlets to carcinoid tumors. Carcinoid tumorlets are most commonly located in the peripheral airways and are often incidentally detected as pulmonary micronodules on chest CT. We report the radiological, bronchoscopic, and pathological findings of a case of carcinoid tumorlets presenting as endobronchial nodules in the left main bronchus. The patient had previously undergone a left lower lobectomy five years earlier for a typical carcinoid tumor. Follow-up imaging revealed new endobronchial nodules, which were subsequently confirmed as carcinoid tumorlets through histopathologic analysis. This case highlights the rare presentation of carcinoid tumorlets in the central airways, emphasizing the importance of recognizing their potential for late recurrence and atypical localization. It underscores the necessity for physicians to be aware that pulmonary neuroendocrine tumors can recur over the long term and may present in a multicentric fashion within the disease spectrum.